Teachers’ attitudes to students’ decision making in Design and Craft education - Þorsteinsson, Gísli; Ólafsson, Brynjar (Menntavísindasvið Háskóla Íslands, 2016)
Decisionmaking skills are an important part of our everyday activities and general education should give opportunities for children to develop such skills. Design and Craft education aims at giving students knowledge and skills necessary in their daily lives. It offers significant opportunities to improve students’ awareness and understanding to make them able to make knowledgeable choices that can enrich their existence and contribute to the growth of their society. Such awareness and understanding equips pupils with the resources to think more critically and to make informed decisions, whether as students, designers, makers or citizens. This article reports an investigation into the attitudes of icelandic teachers regarding students’ decisionmaking in Design and Craft education. The enquiry sought to establish teachers’ understanding of their profession and their roles with regard to students’ decisionmaking, or to explore beliefs and attitudes of Design and Craft teachers regarding their interaction with students while they make design decisions. The investigation looked at the following questions: 1. What decisionmaking opportunities are included in the Design and Craft curriculum in Iceland? 2. What are teachers’ attitudes regarding decisionmaking in Design and Craft education? 3. What decisionmaking opportunities do teachers give to children when working in Design and Craft? The research was conducted using a phenomenographic approach focusing on teachers’ roles and their understanding of the significance of student autonomy at age 12–14, in particular their understanding of the relationship between students’ decisionmaking, the Icelandic National Curriculum for Design and Craft and education in Design and Craft. The enquiry was carried out in two phases during the school year 2010–2011. The first phase included a review of the national curriculum for Design and Craft. The second phase included 10 interviews with practicing Design and Craft teachers to explore attitudes and strategies underpinning their ...